Retrospective review of Duke men's basketball eye care: annual screenings and traumatic injuries. Issue 3 (3rd July 2021) - Wisely, C. Ellis; Legault, Gary; Kim, Terry
ABSTRACT: Objectives: 1) To assess the utility of performing eye screenings for healthy basketball players. 2) To describe the traumatic injuries sustained by competitive college basketball players. Methods: The eye screening examinations of the Duke University Men's Basketball players over six seasons were reviewed retrospectively. Traumatic basketball-related eye injuries amongst Duke University Men's Basketball players over 16 seasons were also reviewed and described. Results: Forty-four total players underwent screening examinations. Thirteen (29.5%) of athletes had uncorrected or under-corrected refractive errors. One athlete was found to have a severe monocular visual deficit secondary to a traumatic injury in childhood, which was significantly mitigated by a contact lens referral. Eight traumatic ocular injuries in eight different athletes, 8.6% of the total roster players in this interval, required ophthalmologic consultation. Most injuries, 7/8, resulted in no permanent visual impairment. However, two severe episodes of injury required operative intervention, and one episode involving a giant retinal dialysis and traumatic optic nerve head avulsion caused severe, permanent visual loss. Most injuries did not result in significant competition time loss, with a median time loss of 5 days (range 0 to 240 days). Conclusion: Screening eye examinations in healthy athletes are beneficial for the identification and treatment of refractive errors. Traumatic basketball-related eye injuries are common and result in a wide array of injuries. Although most basketball-related eye injuries do no result in permanent visual loss, given the potential for severe injury, many basketball-related eye injuries require expert ophthalmic consultation.